Discrimination between glioblastoma multiforme and solitary metastasis using morphological features derived from the p:q tensor decomposition of diffusion tensor imaging. (26th July 2014) - Yang, Guang; Jones, Timothy L.; Barrick, Thomas R.; Howe, Franklyn A.
<x xml:space="preserve">Abstract</x> The management and treatment of high‐grade glioblastoma multiforme (GBM) and solitary metastasis (MET) are very different and influence the prognosis and subsequent clinical outcomes. In the case of a solitary MET, diagnosis using conventional radiology can be equivocal. Currently, a definitive diagnosis is based on histopathological analysis on a biopsy sample. Here, we present a computerised decision support framework for discrimination between GBM and solitary MET using MRI, which includes: (i) a semi‐automatic segmentation method based on diffusion tensor imaging; (ii) two‐dimensional morphological feature extraction and selection; and (iii) a pattern recognition module for automated tumour classification. Ground truth was provided by histopathological analysis from pre‐treatment stereotactic biopsy or at surgical resection. Our two‐dimensional morphological analysis outperforms previous methods with high cross‐validation accuracy of 97.9% and area under the receiver operating characteristic curve of 0.975 using a neural networks‐based classifier. Copyright © 2014 John Wiley & Sons, Ltd.